Dyadic pairs as interview method: Older Singaporeans and their live‐in migrant carers. Issue 3 (16th May 2022) - Liew, Jian An; Ho, Elaine Lynn‐Ee; Yeoh, Brenda S. A.; Huang, Shirlena
Abstract: Dyadic interviewing is a research method that focuses on the interdependent relationship between two people (known as a dyad). Alongside the rise of relational approaches in geography, researchers have taken greater interest in understanding the shared lives of specifically paired individuals. Although paired interviewing presents a way to elicit the constitutive aspects of shared lives, it remains under‐discussed. Based on research methods developed for a project exploring the linked lives of older adults and their migrant carers in Singapore, we examine how intra‐dyadic relations are negotiated during the research process, either reaffirming and/or reconfiguring difference. We introduce a typology that takes into account the role(s) that space, time and mobility play in the organisation of power dynamics. Our proposed classification nuances understandings of dyadic interviewing through drawing out how these trifold dimensions of space, time and mobility mediate interdependent relations. This paper contributes to extant literatures that stress the mutuality of the research process, but with a focus on the social relations of the dyad pairs instead of between the researcher and researched.